ANALISIS KEPUASAN PELANGGAN DALAM LAYANAN PENERBITAN BUKU UNTUK SMK: MENGEKSPLORASI FAKTOR-FAKTOR KUNCI DAN PENDEKATAN PENINGKATAN KUALITAS - Zulvika, Hudria; Rahman, Bima Agustiya (Ma Chung Press, 2025)
The book publishing industry in Indonesia plays a crucial role in supporting the teaching and learning process at various educational levels, including Vocational High Schools (SMK). This study aims to analyze the level of customer satisfaction with book publishing services for SMK, identify key factors influencing satisfaction, and formulate approaches to improving service quality. This research employs a quantitative survey method involving SMK customers as respondents. The collected data is analyzed using descriptive statistics and factor analysis. The findings indicate that overall customer satisfaction falls into the